Blockheads, beagles, and sweet babboos : new perspectives on Charles M. Schulz's Peanuts - Abate, Michelle Ann, 1975- (University Press of Mississippi, 2023)
"Blockheads, Beagles, and Sweet Babboos: New Perspectives on Charles M. Schulz's "Peanuts" sheds new light on the past importance, ongoing significance, and future relevance of a comics series that millions adore: Charles M. Schulz's Peanuts. More specifically, it examines a fundamental feature of the series: its core cast of characters. In chapters devoted to Charlie Brown, Snoopy, Lucy, Franklin, Pigpen, Woodstock, and Linus, author Michelle Ann Abate explores the figures who made Schulz's strip so successful, so influential, and-above all-so beloved. In so doing, the book gives these iconic figures the in-depth critical attention that they deserve and are long overdue. Abate considers the exceedingly familiar characters from Peanuts in markedly unfamiliar ways. Drawing on a wide array of interpretive lenses, Blockheads, Beagles, and Sweet Babboos invites readers to revisit, reexamine, and rethink characters that have been household names for generations. Through this process, the chapters not only demonstrate how Schulz's work remains a subject of acute critical interest more than twenty years after the final strip appeared, but also how it embodies a rich and fertile site of social, cultural, and political meaning"--